Structure and photoactivity for hydrogen production of CdS nanorods modified with In, Ga, Ag-In and Ag-Ga and prepared by solvothermal method. (September 2018) - Soto, E.; Vaquero, F.; Mota, N.; Fateixa, S.; Trindade, T.; Navarro, R.M.; Fierro, J.L.G.
Abstract: This work studies the variation in the photocatalytic properties of CdS derived from the insertion of In, Ga, Ag-In and Ag-Ga in the CdS lattice through solvothermal methodology. Solvothermal synthesis of CdS-M photocatalysts has been succesful for the insertion of Ga 3+, In 3+, Ga 3+ /Ag + and In 3+ /Ag + into the hexagonal crystal lattice of one-dimensional CdS. The insertion of In, Ga, Ag-In and Ag-Ga modifies the band gap and the relative position of EVB. CdS modified with In 3+ or Ga 3+ shows an increase in the band gap and upshift in the relative position of the valence band energy which leads to a low efficiency hydrogen production. The co-addition of Ag + -In 3+ or Ag + -Ga 3+ favours the insertion of Ag + ions into the CdS lattice with narrower band gap. Of all the co-substituted photocatalysts, the CdS-AgGa was the only one that showed a higher photoactivity with respect to the CdS. The increase in the photoactivity of the CdS-AgGa photocatalyst is related to the band gap narrowing and downshift in the relative position of the valence band energy which enhance their visible light absorption and potential for oxidation. The CdS-AgGa photocatalyst shows small segregation of metallic Ag nanoparticles at the surface which also assist in the photoactivity of the sample. Graphical abstract: Image 1 Highlights: Insertion of In 3+ or Ga 3+ in CdS increases its band gap. The co-insertion of Ag + -In 3+ and Ag + -Ga 3+ decreases the band gap of CdS. The CdS-AgGa shows higher photoactivity respect to the CdS.